Relationship between corporate sustainability performance and corporate financial performance: the case of companies from the WIG-ESG Index - Matuszewska-Pierzynka, Agnieszka (Economics and Business Review, 2024)
The essential aim of this paper is to identify the effect of corporate sustainability performance (CSP) on corporate financial performance (CFP) among Polish companies, including all dimensions of sustainability. To achieve this goal, the main research hypothesis, stating that the relationship between CSP and corporate sales performance is positive, has been formulated. The empirical verification of this hypothesis is conducted among 21 companies from the WIG-ESG Index in two different research periods. The basic method of analysis is the panel regression model, which includes corporate sustainability scores as independent variables. All data was retrieved from the Refinitiv Eikon database and the Emerging Market Information Service. The main estimation result is that sales revenues are positively affected by environmental sustainability performance in the long period, while in the short period, governance sustainability performance has a positive impact on the return on sales.